التناص وجمالياته في رواية حيزيا للكاتب واسيني الأعرج - عائشة غراب; حذامي قعيد; فاطمة مسعودي (University of El-oued, 2025)
لقد أصبح تواجد النّصوص السَّالفة، ضمن البنية النصية للإنتاجات الإبداعية أمرا لا مفرَّ منه بالنسبة للمبدع، فلا نص يُكتب من فراغ وما هو إلاَّ تراكمات معرفية تفاعلت فيما بينها وأنتجت نصاً جديدا حافلا بعديد من المزايا، وسميت هذه الظاهرة في الوسط النقدي بـ"التناص" ثم أنَّها نالت حظًّا وافرا من اهتمام كبار النقاد الحداثيين، وهذا ما دعانا إلى اختيارها كموضوع لدراستنا، التي تسعى إلى معالجة هذه الآلية واستنباط جمالياتها في رواية حيزيا زفرة الغزالة الذبيحة كما روتها لالة ميرا لواسيني الأعرج. كونها رواية تناصية بامتياز تزخر بشتى المصادر (التراثية، الأدبية، الدينية والتاريخية) لتذهب بالقارئ إلى الكشف عن النصوص الغائبة والخوض في غمارها، حتى يتمكن من الربط بينها وبين النص الحاضر، كما ويمكن أن يفتح هذا العمل نوافذ بحثية جديدة للدراسات المقبلة كجمالية التراث، تعدد الأصوات في الرواية، مظاهر التجريب في الرواية. Ef The presence of preceding texts within the textual structure of creative productions has become inevitable for the creator; no text is written in a vacuum، but rather it is the result of accumulated knowledge interacting with each other to produce a new text rich in various features. This phenomenon has been termed "intertextuality" in critical circles، and it has received significant attention from leading modernist critics. This has led us to choose it as the subject of our study، which aims to explore this mechanism and extract its aesthetic dimensions in the novel Hayzia: The Sigh of the Slaughtered Gazelle as Told by Lalla Mira by Wassini Al-Araj. This novel is a prime example of intertextuality، filled with various sources (heritage، literary، religious، and historical)، leading the reader to uncover the absent texts and delve into them، enabling them to establish connections between them and the present text. Moreover، this work can open new research avenues for future studies، such as the aesthetics of heritage، polyphony in the novel، and the manifestations of experimentation in the novel.
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: الجمالية، التناص، التراثي، الأدبي، الديني، التاريخي، حيزيا، واسيني الأعرج; aesthetics; intertextuality; heritage; literary; religious; historical; Hayzia; Wassini Al-Araj